Sustainable Transportation Infrastructures in Iowa—Goals and Practices - Lee, Hosin; Moon, Byungkyu; Lee, Jeongbeom (Infrastructures (Basel), 2024)
The need to incorporate sustainability principles and practices is increasing for environmental and economic reasons. It is imperative to identify and operationalize sustainability strategies into core administrative, planning, design, construction, operational, and maintenance activities for the transportation infrastructure systems by integrating sustainability into decision-making processes. The primary goal of this study is to develop an implementation plan for achieving more sustainable transportation infrastructure systems in Iowa. This research aims to guide the adoption of sustainable strategies, balancing cost, performance, and environmental impact in transportation infrastructure development. This paper presents efforts to develop a methodology for identifying the best sustainable practices for implementation in transportation infrastructure practices in Iowa by surveying state DOTs to learn about their sustainability goals and practices, identifying existing sustainability attributes and sustainable practices, and developing a GIS database where construction, materials and performance data of sustainable practices can be stored and analyzed.